2018
DOI: 10.1101/496612
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single cell RNA-Seq reveals distinct stem cell populations that drive sensory hair cell regeneration in response to loss of Fgf and Notch signaling

Abstract: Loss of sensory hair cells leads to deafness and balance deficiencies. In contrast to mammalian hair cells, zebrafish ear and lateral line hair cells regenerate from poorly characterized, proliferating support cells. Equally ill-defined is the gene regulatory network underlying the progression of support cells to cycling hair cell progenitors and differentiated hair cells. We used single cell RNA-Sequencing (scRNA-Seq) of lateral line sensory organs and uncovered five different support cell types, including qu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 101 publications
2
9
0
Order By: Relevance
“…and fzd7a/b are strongly expressed in support and not hair cells in neuromasts ((Mark E. Lush, 2018), Fig. 6, Fig.…”
Section: Pcp and Wnt Signaling Pathways Control Two Different Aspectsmentioning
confidence: 99%
“…and fzd7a/b are strongly expressed in support and not hair cells in neuromasts ((Mark E. Lush, 2018), Fig. 6, Fig.…”
Section: Pcp and Wnt Signaling Pathways Control Two Different Aspectsmentioning
confidence: 99%
“…Figure S3A shows in which cell types different placodal genes are enriched. Prior studies showed that Notch and Fgf signaling are downregulated to allow for Wnt-dependent cell proliferation (Lush et al, 2019;Romero-Carvajal et al, 2015). Notch downregulation is also required to initiate hair cell differentiation (Ma et al, 2008;Romero-Carvajal et al, 2015;Wibowo et al, 2011).…”
Section: Module 1 (0min): Modulation Of Progenitor/stem Cell Maintenance/placodal and Injury/inflammatory Response Genesmentioning
confidence: 99%
“…To gain a better understanding of the lineage trajectories that central support cells (central SCs) undergo during regeneration and to identify associated genes, we aligned central support-, progenitor-and hair cells along pseudotime using Monocle 3 (Cui et al, 2020;Qiu et al, 2017;Trapnell et al, 2014). We chose to limit the analysis to these cell types, as in vivo lineage tracing showed that central support cells are the direct precursors to hair cells (Lush et al, 2019). Although D/V and A/P cells can also give rise to hair cells (Romero-Carvajal et al, 2015;Thomas and Raible, 2019;Wibowo et al, 2011), it still needs to be determined whether A/P and D/V cells first acquire a central support cell fate.…”
Section: Pseudotime Analysis Indicates That Central Support Cells Either Differentiate Into Hair Cells or They Re-express Support Cell Gementioning
confidence: 99%
See 2 more Smart Citations